DETERMINAN FAKTOR YANG MEMPENGARUHI KAPASITAS PARU PADA PEKERJA PENGRAJIN KERAMIK DI KECAMATAN KLAMPOK BANJARNEGARA - Dany Dwi Noviantio; Suryanto Suryanto; Nur Ulfah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2014)
ABSTRACT The impact of industrial pollution may disrupt workers' health ceramics and air pollution. The pollutants come from dust generated from the sanding process ceramics. Dust can cause effects such as impaired lung function when exceeding a threshold level and a long exposure. The purpose of this study was to analyze the effect of age, years of service, nutritional status and the use of a mask with a lung capacity of potters working part sanding in sub-district PurwarejaKlampoksanding.This research is explanatory research with cross sectional approach. Data were analyzed using multiple regression test. The population consists of 24 people with the female worker. Instrument in this study is a spirometer and PDS (Personal Dust Sampler). Results of the bivariate analysis are R value <R table regression (0.404) which means that there is no effect of age with a capacity of lung function, there is no influence tenure with lung function capacity , while the frequency of use of masks and nutritional status R value> R table regression (0.404) it can be concluded that no effect of nutritional status on lung capacity, there is a relationship with the frequency of the use of masks lung function capacity. Are suggested to the owner of the company that requires workers to wear masks while working.while the employee should be disciplined to wear a mask, eating a nutritious and balanced diet and maintain a healthy weight. Keywords: Lung Capacity, Craftsman Ceramics Kesmasindo, Volume 7, Nomor 1 Juli 2014, Hal 1-11